Heat shock transcription factor-mediated thermal tolerance and cell size plasticity in marine diatoms - Dan Huang; Cai-Qin Cheng; Hao-Yun Zhang; Yun Huang; Si-Ying Li; Yi-Tong Huang; Xue-Ling Huang; Lu-Lu Pei; Zhaohe Luo; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Nature Communications)
Abstract Diatoms are a crucial component of marine ecosystems, recognized for their broad environmental adaptability and wide temperature tolerance. However, the molecular mechanisms underlying their adaptability to diverse temperatures are unknown. In this study, we discover that heat shock transcription factors (HSFs) are potentially important for thermal tolerance in diatoms. Our study focuses on PtHSF2, annotated as HSF2 in Phaeodactylum tricornutum’s genome, which is ubiquitous in diatoms. Overexpression of PtHSF2 markedly enhances thermal tolerance and increases cell size; causes significant differential expression of several genes, including cell division cycle protein 45-like (PtCdc45-like), ATM (ataxia telangiectasia mutated), ATR (ataxia telangiectasia and Rad3-related), light-harvesting complex protein 2 (Lhcx2), and fatty acid desaturase. Cleavage Under Targets and Tagmentation (CUT&Tag) and CUT&Tag-qPCR analyses demonstrate that PtHSF2 directly targets and upregulates PtCdc45-like and Lhcx2 while downregulating ATP-binding cassette transporter. Functional validation of PtCdc45-like shows that its overexpression results in larger cell size, enhances antioxidant capacity, and improves cell survival at elevated temperatures. Collectively, our findings elucidate the molecular mechanism by which PtHSF2 mediates high-temperature tolerance in diatoms and validate the functions of its target gene PtCdc45-like. These results highlight the importance of HSFs in diatom temperature adaptation and provide insights into temperature acclimation in microalgae.